Effect of Addition “Attack” Detergent at Different Concentration and Exposure Time on Heterotrophic Bacterial Growth in Sea Water - Roiman Pakpahan; Irwan Effendi; Nursyirwani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to determine the effect of “Attack” detergent addition at different concentration and exposure time on heterotrophic bacterial growth in sea water. The research was conducted from February to April 2017 used experimental method. The results showed that the highest number of heterotrophic bacteria was observed on the A5 day 1st exposure treatment of 6,69 x 107 (CFU/ml) and the lowest was in the 16th day of exposure treatment of 0,098 x 107 (CFU/ml). At day 1st, the value of the correlation coefficient (r) obtained by 0.277 showed the relationship between two variables with positive linearity, while day 6th to day 21th, the correlation coefficient (r) are 0,982, 0,9426, 0,9778 and 0,986, showed the relationship between moderate two was very strong variables with negative linearity. The regression relationship between exposure time and bacterial growth showed a strong correlation with negative linearity, where the coefficient value (r) was 0,87. Significant treatment of detergent concentration that was equal to 0,00 and exposure time that was equal to 0,00 < α (0,05). The bacterial growth on treatment A1 (control) was significantly different with treatment A2, A3, A4 and A5. Bacterial growth at day 1st was significantly different from 6th, 11th, 16th and day 21th. The result of this research showed that there were a effect of “Attack” detergent addition with different concentration and exposure time to the growth of heterotrophic bacteria in seawater.Keyword: Detergent, Concentration, Exposure, Growth, Heterotrophic Bacteria